2017
DOI: 10.1080/02705060.2017.1323682
|View full text |Cite|
|
Sign up to set email alerts
|

Algicidal activity of the bacterium, Pseudomonas fluorescens SK09, to mitigate Stephanodiscus hantzschii (Bacillariophyceae) blooms using field mesocosms

Abstract: The main goal of this study was to characterize mortality and trophic interactions of Stephanodiscus hantzschii (small centric diatoms) in the presence of an algicidal bacterium, Pseudomonas fluorescens HYK0210-SK09 (SK09) in outdoor mesocosm experiments with an extremely low temperature and also in direct application in a river. SK09 at an inoculation density of 5 £ 10 6 cells/mL (Experiment 1) and SK09 cells immobilized in activated carbon polyvinyl alcohol sponge carriers (Experiment 2) did not appear to at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 18 publications
(30 reference statements)
0
8
0
Order By: Relevance
“…isolate and the microalga Ulva prolifera and found distinct bacterial genomic traits contributing to their symbiotic relationship [ 68 ]. In contrast, members of the bacterial family Pseudomonadaceae have also been reported to be able to produce algicidal compounds, indicating the specificity of growth-promoting and detrimental effects on different algae [ 69 , 70 ]. These findings are also reflected by the implemented co-occurrence network analyses.…”
Section: Discussionmentioning
confidence: 99%
“…isolate and the microalga Ulva prolifera and found distinct bacterial genomic traits contributing to their symbiotic relationship [ 68 ]. In contrast, members of the bacterial family Pseudomonadaceae have also been reported to be able to produce algicidal compounds, indicating the specificity of growth-promoting and detrimental effects on different algae [ 69 , 70 ]. These findings are also reflected by the implemented co-occurrence network analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Only a few investigations have been conducted in open water in the field. To date, all reports on field applications of algicidal bacteria involved the use of bacterium Pseudomonas fluorescens HYK0210-SK09 (SK09) in river enclosures ( Jung et al, 2010 ; Kang et al, 2011 ; Noh et al, 2017 ). These reports underline the necessity of conducting field trials to confirm activity under conditions that may differ from those of laboratory culture experiments.…”
Section: Application Strategies For Control Of Harmful Algal Bloomsmentioning
confidence: 99%
“…These reports underline the necessity of conducting field trials to confirm activity under conditions that may differ from those of laboratory culture experiments. Although SK09 exhibited strong species-specific algicidal activity against the winter-blooming harmful diatom Stephanodiscus hantzschi in laboratory culture experiments and indoor mesocosm studies ( Jung et al, 2008 , 2010 ), experiments conducted in less controlled field environments yielded inconsistent results ( Jung et al, 2010 ; Kang et al, 2011 ; Noh et al, 2017 ). Temperature likely played a role in the efficacy of SK09 along with other factors, including the high concentrations of algicidal bacteria required ( Seong and Jeong, 2013 ).…”
Section: Application Strategies For Control Of Harmful Algal Bloomsmentioning
confidence: 99%
“…While both the bacteria and the extracellular substances successfully controled single-species algal blooms in the laboratory conditions, this does not necessarily represent their applicability in the natural environment, which is more complex and variable [ 14 ]. In-situ mesocosm studies were performed to assess the risks and determine the ecological relevance of the laboratory-identified effects [ 13 , 15 ]. Abiotic factors such as light, pH, nutrient flux, and temperature influence the interaction between algae and bacteria [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies claimed that low-nitrogen conditions reduce the algal growth rate, subsequently increasing the intracellular lipid contents for energy storage [ 18 ]. It was also reported that the algicidal activity of algicidal strain Pseudomonas fluorescens SK09 is strongly associated with changes in nutritional status and consequent succession of phytoplankton species [ 15 ]. Despite the importance of nutritional status to the algicidal activity, information of algicidal activities on the different nutritional status is still lacking.…”
Section: Introductionmentioning
confidence: 99%